We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
575
1
avatar+164 

Given that $f(3)=5$ and $f(3x)=f(x)+2$ for all $x$, find $f^{-1}(11)$.

 May 22, 2018
 #1
avatar+101431 
+2

If  f(3)  = 5   and    f(3x)  = f(x) + 2, then .....

 

f(3x)  = f(3) + 2     implies that x  = 3

 

So

 

f(3 * 3)  = f(3) + 2

f(9)  =  5 + 2

f(9)  = 7

 

And

f(3x)  = f(9) + 2   implies that  x  = 9...so.....

f(3*9) = f(9) + 2

f(27)  = 9

 

And

 

f(3x)  = f(27) + 2   implies that x  = 27

f(3 * 27)  = f(27) + 2

f(81)  = 9 + 2

f(81) = 11

 

And   (81, 11)  is on the original graph  .....so  (11, 81)  is on the inverse

 

So

 

f-1(11)  =  81

 

 

cool cool cool

 May 22, 2018

10 Online Users

avatar
avatar
avatar